2019
DOI: 10.1002/jcla.23096
|View full text |Cite
|
Sign up to set email alerts
|

Low serum miR‐223 expression predicts poor outcome in patients with acute myeloid leukemia

Abstract: Background Identification of biomarkers for acute myeloid leukemia (AML) is important for treating this malignancy. Recent studies have reported that microRNAs (miRNAs) are stably detectable in the blood/plasma and can be used as biomarkers for various types of cancer including AML. The aim of this study was to analyze miR‐223 level in serum as a potential indicator for AML diagnosis and prognosis prediction. Methods Quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) was used to detect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, few studies have explored the role of miR-223 in AML. Previous studies demonstrated low miR-223 expression in patients with AML, especially in those with a poor prognosis (11,12). Moreover, a marked increase in miR-223 expression was reported in patients with AML after treatment, regardless of whether complete remission was achieved or not (12).…”
Section: Microrna-223 Overexpression Suppresses Protein Kinase C ε Ex...mentioning
confidence: 90%
“…However, few studies have explored the role of miR-223 in AML. Previous studies demonstrated low miR-223 expression in patients with AML, especially in those with a poor prognosis (11,12). Moreover, a marked increase in miR-223 expression was reported in patients with AML after treatment, regardless of whether complete remission was achieved or not (12).…”
Section: Microrna-223 Overexpression Suppresses Protein Kinase C ε Ex...mentioning
confidence: 90%
“…[104], [105], [106], [107] miR-142 IDH mutation ASH1I, CTNNB1, HOXA [108], [109] miR-155 FLT3+, M4, M5 PU.1, PI3K-AKT, SHIP1 [110], [40] miR-181 M1, M2, M3, CEBPA mutation CAMKK1, CTDSPL, HMGB1, KRAS, MCL-1, MAPK1, NRAS, PRKCD-P38-C/EBPα [111], [24], [112], [66] miR-196 MLL-AML (HOX), FLT3+, M4, M5 ANXA1, ERG, FAS, HOXA9, MEIS1 [51], [113] miR-199 NPM1, M5 DRAM1, ERK, HIF-1α, HOXA7, HOXB6, KRAS-AKT [114], [115] miR-210 Myelodysplastic syndrome C/EBPα, HIF-1α, SHIP1 [42], [43] miR-223 All FAB subtypes E2F1, FBXW7, TP53 [116], [117], [57], [59] miR-378 AML1-ETO, M2, t(8;21) EPOR, FUS1, GZMB [118], [119] miR-451 C-MYC, MDR1, YWHAZ-AKT [62] miR-486 DS-AML PI3K-AKT, SOCS2-JAK-STAT [120], [50] AHS1l, ASH1-like histone lysine methyltransferase; ANXA1, annexin 1; CCND2, cyclin D2; CCNG1, cyclin G1; CDH1, cadherin 1; CDH7, cadherin 7; CDK3/6, cyclin-dependant kinase 3/6; CDX2, caudal-type homeobox 2; CEBPA, CCAAT enhancer binding protein 4; CTNNB1, catenin beta 1; DRAM1, DNA damage regulated autophagy modulator 1; eIF4G2, eukaryotic translation initiation factor 4 gamma 2; EPOR, erythropoietin receptor; E2F3, E2F transcription factor 3; E2F7, E2F transcription factor 7; ERK, extracellular signal-regulated kinase; ERG, ETS transcription factor ERG; ETS-1, ETS proto-oncogene; FOXO1/3, forkhead box O1/O3; FUS1, tumour suppressor 1 calcium regulator; GZMB, granzyme B; ID2, inhibitor of DNA binding 2; JAG1, jagged 1; KRAS, KRAS proto-oncogene; MAPK1, mitogen-activated protein kinase 1; NFκB, nuclear factor kappa B; NKIRAS2, NFκB inhibitor-interacting Ras-like 2; NRAS, NRAS proto-oncogene; P27, cyclin-dependant kinase inhibitor 1B; PDK1, pyruvate dehydrogenase kinase 1; PU.1, Spi-1 proto-oncogene; SIRT1, Sirtuin 1; SOCS2, suppressor of cytokine signalling 2; STMN1, stathmin 1; TET2, Tet methylcytosine dioxygenase 2; TNFα, tumour necrosis factor alpha; TP53, tumour protein 53; TSPAN3, tetraspanin 3; YWHAZ, protein zeta. as a treatment for polycythaemia vera that is being used in clinical trials [28].…”
Section: Mir Targets For Aml Therapyunderexpressed Mirsmentioning
confidence: 99%
“…miR-223 underexpression also leads to overexpression of another of its targets, F-box and WD repeat domain containing 7 protein (FBXW7), which was demonstrated as contributing to proliferation and reduced apoptosis in AML[58]. A recent study determined that low miR-223 was a significant independent indicator of poor OS in AML patients while an elevated expression of miR-223 was more prevalent in patients with CR[59]. miR-451 is involved in the late-stage maturation of erythroid cells and is unique amongst miRNAs.…”
mentioning
confidence: 99%
“…In acute myeloid leukemia (AML), a cancer of the myeloid line of blood cells, miR‐223 show the opposite trend, with low levels of miR‐223 correlating with poor prognosis of the patients (Gentner et al, 2015 ; Guopan Yu et al, 2020 ). Pulikkan et al discovered an autoregulatory negative feedback loop linking C/EBPα, miR‐223 and E2F1 normally regulating granulopoiesis and dysregulated in AML (Pulikkan et al, 2010 ).…”
Section: Mir ‐223 In Cancer Onset and Progressionmentioning
confidence: 99%
“…Moreover, low serum levels of miR‐223 have been correlated with aggressive clinical variables and shorter survival rates. Interestingly, AML patients display a significant increase in miR‐223 levels after treatment, suggesting a strong reliability of miR‐223 serum levels as diagnostic and prognostic biomarker in acute myeloid leukemia patients (Guopan Yu et al, 2020 ).…”
Section: Mir ‐223 As Potential Biomarkermentioning
confidence: 99%